Community Driven Initiatives for The Enrolment of Children with Disability in Ghana - Duorinaah , Eric (International Journal of Developing Country Studies, 2023)
Purpose: The purpose of this study was to determine nature of participation and the contributions local communities make in the enrolment of children with disability in schools in the Jirapa District of Ghana. The study was anchored on the concern that inspite of the importance of inclusive education, globally, 258 million children, majority with disability are out of school. About 400,000 of these are in Ghana. Methodology: A case study design was employed with a sample size of 72 respondents drawn from parents who had their children in the basic public schools, community leaders, School Management Committees and Parent Teacher Associations, head teachers, class teachers and pupils from 10 communities and their public primary schools. Through thematic analysis of the qualitative data and descriptive statistics of enrolment records the study the awareness and specific contributions and best practices from community members and actual number of children with disability who have been enrolled in school. Findings: The study revealed a high level of community awareness regarding children with disability while community participation and their contributions manifested in mapping, house to house enrolment drives and sensitization forums as these addressed stigma and discrimination against children with disability and their families, ultimately resulting in the former's enrolment in school. Contribution to theory, practice and policy: The findings provide more empirical evidence regarding specific contributions of local communities in the realisation of the provisions of Ghana's Inclusive Education Policy. Globally, best practices such as community mapping as revealed by the study can contribute significantly to the attainment of the Sustainable Development Goal 4 which seeks to ensure inclusive and equitable quality education and promote lifelong learning opportunities for all.